Matematyka jako fundament nowoczesnych finansów. Analiza problemu na podstawie doświadczeń związanych z uruchomieniem specjalności Master Program Quantitative Asset and Risk Management (ARIMA) - Chrzan, Piotr; Dziwok, Ewa (Mathematics as a foundation of modern finance, 2010)
The aim of the article is to stress the important role of quantitative methods in finance development. An analysis of the Nobel Price winners‘ curricula shows that mathe-matics has played the crucial role in their education at universities of applied sciences. The analysis is also based on our experience connected with a specialization Master Program Quantitative Asset and Risk Management (ARIMA) which was implemented in Finance and Accounting courses at the University of Economics, Katowice
Didactics of Mathematics, 2010, Nr 7 (11), s. 15-22
Keywords: didactics of mathematics; quantitative methods